Emergence and initial growth of Schizolobium parahyba var. amazonicum as a function of sowing depth in the amazon biome - Dionisio, Luiz Fernandes Silva; Sousa, Jefferson Nascimento de; Santos, Henderson Duarte dos; Milhomem, Camila de Almeida; Silva, Alinne da; Oliveira Junior, Jose Carlos de [UNESP] (Univ Federal Rural Pernambuco, 2022)
The direct seeds sowing reduces the costs of implanting of forest stand, but it is necessary to study the ideal sowing depth, since this factor can affect the emergence and initial growth of the seedlings. The aim of this study was to evaluate the influence of different sowing depths on emergence, survival, and initial growth of Schizolobium parahyba var. amazonicum in the field conditions. A randomized block design was adopted, with five treatments and five replications, of 20 seeds each. The treatments were different depth, as follows: 5 cm (T1), 10 cm (T2), 15 cm (T3), and 20 cm (T4). Were evaluated the percentage of emergence, average time and emergence speed index, collar diameter, number of leaves, aerial part height, degree of slenderness and survival rate of seedling at 120 days after sowing. The results showed that emergence started two days after sowing, stabilizing on the 13th day. The depths of 5, 10, and 15 cm showed satisfactory results in terms of emergence percentage, survival rate and initial growth. The sowing depth of 10 cm was the best results for the variables studied. The best result for the average time and emergence speed index were obtained at depth of 5 cm. Direct sowing of S. parahyba is a viable method to be implemented by small and medium farmers, aiming to reduce costs by eliminating the nursery phase. The ideal seeding depth for the emergence, survival and initial growth of S. parahyba is at a depth of 10 cm.
Keywords: Amazon rainforest; direct seeding; forest seeds; Paragominas; Parica